Reflexões de lideranças Macuxi e Wapichana sobre as contribuições das TICs para os projetos indígenas locais - Santos, Raimunda Maria Rodrigues (Universidade do Vale do Rio dos Sinos, 2016)
This thesis has as its theme the use of information and communication technologies by leaders of Macushi and Wapishana ethnic groups to assist in their social relationships. This theme has raised the debate on issues related to cultural diversity, changes in consumption patterns, among other aspects of local sustainability, which contributed to the understanding of the presence of modernity in the communities where the subjects of this research live. Thus, the objective was to analyze the perception of the indigenous leaders on the implications of the use of information and communication technologies in everyday social practices of their communities and in the monitoring of their relations in different socio-political and cultural contexts. To collect data, we used a field book and audio recordings in which the narratives of indigenous leaders were recorded, highlighting three leaders of each ethnic group. The interviews were conducted during random meetings conducted during August 2014 to June 2016, and the texts formed the body of research. The analysis of the records followed the principles recommended by the phenomenological method, with interpretive approach, seeking to establish a dialogue between the reflections of respondents on their experiences as leaders and the theoretical foundations of leadership, reflexivity and in technology of information and communication. The narratives mobilized different reflexivities where history of struggle in defense of the land, identity and autonomy, among other original rights, is constantly evoked not only the motto of a historical moment, but as a driving foundation of communitarian life among the Macushi and Wapishana people. It was evident that the leaders fear that the use of information and communication technologies by the young indigenous people may help to widen the chasm in community relations; as a result, they advocate that communities must develop strategies for the reflexive monitoring of such use. On the other hand, they also recognize that the empowerment through information and communication technologies will strengthen actions in favor of the autonomy of their communities, working in favor of the indigenous resistance by connecting Macushi and Wapishana people in an ethnic social network, confirming in this way, the thesis that these technological resources serve to support the strengthening of ethnic identity/cultural diversity of these indigenous peoples.
Keywords: Movimento indígena; Liderança; Tecnologia de informação e comunicação; Reflexividade; Indigenous movement; Leadership; Information and communication technology; Reflexivity; ACCNPQ::Ciências Humanas::Sociologia